GPS data from Taku Glacier, Alaska, 2014-2016 - Jason Amundson; Martin Truffer (Arctic Data Center, 2018)
This project investigated the feedbacks between glacial erosion and glacier dynamics at Taku Glacier, Alaska, which is currently in the advancing phase of the tidewater glacier cycle. We measured the spatial and temporal patterns of sediment erosion, properties of basal till, basal water pressure, basal motion, ice deformation, surface velocities, surface mass balance, and changes in surface elevation and terminus position. Data was collected from spring 2014 through fall 2016. The project consisted of time-lapse photography, borehole instrumentation, GPS surveys, active seismics, and basic meteorological measurements. All field work was conducted close to the glacier terminus. This data set contains GPS data collected at 6 sites on the glacier (C1, C2, SUP, SLFT, SRIT, and SDWN) and one site located in the proglacial outwash (TAKU) that served as a base station.